Changes in main pulmonary artery diameter during follow‐up have prognostic implications in pulmonary arterial hypertension. Issue 8 (17th May 2017) - Tonelli, Adriano R.; Johnson, Scott; Alkukhun, Laith; Yadav, Ruchi; Dweik, Raed A.
ABSTRACT: Background and objective: A dilated pulmonary artery (PA) is a common finding in patients with pulmonary arterial hypertension (PAH). Little is known on the variations in PA size over time and whether these changes track with disease severity and/or predict long‐term survival. Methods: We included patients with PAH who had at least two computed tomography (CT) scans of the chest done on different visits. Both scans matched the use of i.v. contrast. Results: Pairs of CT scans were compared in 113 PAH patients. During a median (interquartile range (IQR)) time difference between scans of 8 (IQR: 3.5–20.0) months, we noted an increase in main PA diameter of 0.5 ± 1.8 mm (mean ± SD) ( P  = 0.008). When CT scans were performed >12 months apart ( n  = 47), the main PA diameter increased or decreased by >1 mm in 40% and 13% of the patients, respectively. An increase in main PA diameter was associated with lower PA compliance, higher right ventricular (RV) systolic pressure, worse RV function and a decline in 6‐min walk distance. During a median (IQR) follow‐up of 33 (IQR: 4.5–47) months, 53 (46.9%) patients died. The change in PA diameter was a significant predictor of mortality (hazard ratio (HR) per mm increase: 1.33 (95% CI: 1.11–1.61), P  = 0.002) when adjusted for difference in time and slice thickness between CT scans, age, gender, PAH aetiology and pulmonary vascular resistance. Conclusion: In PAH patients, an increase in CT‐derived main PA diameter over time is associated with progression in pulmonary pressures, RV dysfunction, a decline in functional capacity and higher mortality. Abstract : See related Editorial It remains unclear whether the increase in main pulmonary artery (PA) diameter over time has prognostic implications in patients with pulmonary arterial hypertension. In the present study, we found that an increase in main PA diameter was associated with higher PA pressures, lower PA compliance, worse right ventricular function and reduced survival.